Mutation differences in circulating tumor DNAs from non-small cell lung cancer patients between Uygur and Han populations. Issue 4 (29th January 2021) - Wang, Yuli; Li, Jing; Huang, Jian; Wu, Chaoqun; Li, Li; Gong, Ping
Abstract: Background: The incidence of non-small cell lung cancer (NSCLC) in Uygur population is gradually increasing recently. In view of the great diagnostic and prognostic values of cell-free DNAs (cfDNA) detection, this study focus on a liquid biopsy to explore the value of cfDNA mutation in healthy and NSCLC patients in 2 ethnicities. Methods: The concentration and sequencing of cfDNA in NSCLC and healthy subjects was assessed with a standard information analysis procedure, including detection, annotation, and statistical analysis. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were conducted to analyze the function of mutant genes and related pathways. Totally, 133 subjects, including 35 Uygur NSCLC patients, 10 Uygur healthy subjects, 63 cases of Han NSCLC patients and 25 Han health control, were admitted to the hospital. Results: There were a lower proportion of adenocarcinoma and higher percentage of smoking rate for Uygur patients. For cfDNA level between NSCLC and healthy subjects, Han patients exhibited sharp increase while there was no statistical difference in Uygur population. In addition, the mutation frequency of cfDNA in Han patients (72.6%) was significantly higher than Uygur patients (45.7%). There were 5 gene mutations only found in Han patients and ABCC11 showed a higher mutation frequency in Uygur population as a common one. Finally, Go and Kyoto Encyclopedia of Genes and Genomes analysis showed apprent functional enrichments and pathway changes between 2 ethnicities. Conclusion: There existed distinct distributions of cancer subtypes, smoking proportion, cfDNA level, and mutation patterns between Han and Uygur patients. The results may be a useful tool in NSCLC patients' diagnosis as well as individualized therapy between ethnicities in future. Abstract : Supplemental Digital Content is available in the text